2018
DOI: 10.1039/c7fo01570d
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomics approach to the intestinal microbiome structure and function in high fat diet-induced obesity mice fed with oolong tea polyphenols

Abstract: To investigate the modulatory effect of oolong tea polyphenols (OTP) on intestinal microbiota, OTP was prepared by column chromatography and its influence on the gut flora structure was analyzed by high-throughput sequencing with a human flora-associated high fat diet (HFD) induced obesity mouse model. We observed a robust increase in bacterial biodiversity and the abundance of genera known to be butyrate- and acetate-producing bacteria. A large increase in Bacteroidetes with a decrease in Firmicutes was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 36 publications
7
79
0
Order By: Relevance
“…A cranberry extract, however, was unable to reverse the high‐fat, high‐sugar (HF/HS)‐induced decline of Bacteroidetes (Anhe et al, ). In contrast, a decrease in the Firmicute/Bacteroidetes ratio was observed in mice fed a high‐fat diet supplemented with oolong, green, or black tea polyphenols (Cheng et al, ; Henning, Yang, et al, ) or grape polyphenols (Roopchand, Carmody, Kuhn, & Moskal, ). Mice fed a HF/HS diet alone or in conjunction with a commercial extract of pomegranate by‐product (POMx, POM Wonderful) had very low levels (<0.01%) of the genus Bacteroides that dropped to undetectable levels upon POMx treatment and high relative abundance of the family S24‐7 (58%), a member of the Bacteroidetes that was not altered by POMx treatment (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A cranberry extract, however, was unable to reverse the high‐fat, high‐sugar (HF/HS)‐induced decline of Bacteroidetes (Anhe et al, ). In contrast, a decrease in the Firmicute/Bacteroidetes ratio was observed in mice fed a high‐fat diet supplemented with oolong, green, or black tea polyphenols (Cheng et al, ; Henning, Yang, et al, ) or grape polyphenols (Roopchand, Carmody, Kuhn, & Moskal, ). Mice fed a HF/HS diet alone or in conjunction with a commercial extract of pomegranate by‐product (POMx, POM Wonderful) had very low levels (<0.01%) of the genus Bacteroides that dropped to undetectable levels upon POMx treatment and high relative abundance of the family S24‐7 (58%), a member of the Bacteroidetes that was not altered by POMx treatment (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports about the tea administration and its effects on gut microbiota. Administration of oolong tea polyphenols for 4 weeks can improve the fecal microbiota diversity in high‐fat diet‐induced obesity mice, and also decreased Firmicutes/Bacteroidetes (Cheng et al., ), which is reported to be closely related with the development of obesity and insulin resistance induced by high‐fat diets. Furthermore, green and black teas also decreased cecum Firmicutes and increased Bacteroidetes (Henning et al., ).…”
Section: Tea Chemistrymentioning
confidence: 99%
“…Several studies over the last decade reported that TP and intestinal microbiota could control obesity and related metabolic disorders (Carrera‐Quintanar et al, ). TP have the activity of adjusting human‐specific intestinal beneficial bacteria, which is effective for the improvements of host health (Cheng et al, ). In addition, the anticancer effect of TP has been widely reported (Sajilata, Bajaj, & Singhal, ).…”
Section: Introductionmentioning
confidence: 99%